Do benefits of expanded midstream activities in crop value chains accrue to smallholder farmers? Evidence from Zambia. (July 2021) - Nuhu, Ahmed Salim; Liverpool-Tasie, Lenis Saweda O.; Awokuse, Titus; Kabwe, Stephen
Highlights: We estimate smallholder welfare effects of non-formal contract midstream activities in Zambia's soybean value chain. Fixed Effects and instrumental variable estimators are used to address the endogeneity of smallholder crop sale decisions. Smallholders are included in and benefitting from Zambia's soy industry expansion, able to earn 34% higher crop income. Higher total income and lower poverty is only observed for medium scale smallholders operating 5–20 ha. Abstract: The rapid expansion of food supply chains across Africa has created huge market opportunities for farmers. In particular, the rise of numerous enterprises engaged in food processing and trading in the 'midstream' of value chains is promising. Compared to large enterprises using formal contracts, midstream enterprises not using contracts are considered more accessible to small-scale farmers. However, the extent to which economic benefits of the recent expansion of these non-contract opportunities in Africa is inclusive of smallholder farmers is uncertain and largely unexplored. This is critical for the global debate on poverty and sustainable economic development as the share of agricultural land under smallholder farmers, who constitute a significant proportion of the world's poor is still rising. This paper contributes to this thin literature with evidence from Zambia, where a growing demand for meat has stimulated growth of the soybean industry. We use nationally-representative panel survey data from Zambia to explore the welfare effects of smallholder engagement with soybean traders and processors in non-contractual arrangements. The analysis uses fixed effects and instrumental variables estimation techniques to address the endogeneity of the smallholder decision to sell to large-scale traders and processors. We find significant positive crop income effects of selling to soybean large-scale traders and processors on all smallholders. However, the observed effects only translate into higher total household incomes and poverty reduction for medium-scale smallholders (operating 5 ha- 20 ha) but not for small-scale smallholders operating less than five hectares. The positive crop income effects are mainly driven by the opportunity to sell more although small-scale smallholders receive a price premium from selling to large buyers. These results suggest that the recent expansion of the soybean industry in Zambia is benefiting smallholder farmers but not necessarily enough to move the smallest of these farmers out of poverty.